Assessing the effectiveness of projects supporting on-farm conservation of native crops: evidence from the high Andes of South America - Bellon, M.R.; Gotor, Elisabetta; Caracciolo, Francesco (Elsevier, 2015)
This paper presents an approach for assessing the effectiveness of projects aimed at creating incentives for smallholder farmers to continue maintaining crop diversity under evolution on their farms in relevant centers of genetic diversity—a process known as on-farm conservation. It is applied to five projects involving native crops in the High Andes of South America. Results show evidence that projects have been effective at supporting farmers to maintain crop diversity on-farm while generating positive livelihood outcomes. Implications and challenges of both the approach and the results for sustainable use and conservation of crop biodiversity are discussed.